Exceptionally Large Clutches in Two Raptors Breeding in Nest Boxes - Orozco Valor, Paula Maiten (2016)
Nest site availability may limit secondary cavity-nesters because they are unable to create their own cavities and thus are forced to use existing cavities. Nest boxes can help to overcome this limitation but they can affect clutch size. In South America, the Ferruginous Pygmy-Owl (Glaucidium brasilianum) clutch size usually ranges from two to five eggs. The American Kestrels (Falco sparverius) clutch size usually ranges from four to six eggs. In South America all recorded clutch sizes in the late species did not exceed five eggs. Here we present records of same season exceptionally large clutches for both species breeding in nest boxes put up for American kestrels in central Argentina. Every year since 2011-2012 a maximum from 24 to 104 nest boxes have been monitored. In the 2014-2015 breeding season one of the boxes was occupied by Ferruginous Pygmy-owls. This pair laid an exceptional clutch of seven eggs (to our knowledge the largest clutch ever recorded for the species in South America).Six nestlings fledged successfully. In the same season, unusually large clutches were recorded for American Kestrels too, with six clutches of six eggs, three clutches of seven eggs and one clutch of eight eggs (as far as we know, the largest ever recorded globally for the species). However, hatching never exceeded six individuals in any of the exceptional clutches. Extremely large clutches reported here are probably the result of an exceptionally good year in food resources for these two species. The unusual clutch sizes may have been also related to breeding in spacious nest boxes and in the case of the American Kestrels could also be favored by the larger size of the South American subspecies.